From binational society to Jewish state : federal concepts in Zionist political thought, 1920-1990, and the Jewish people - Gorni, Yosef (Jewish identities in a changing world ;, 2006)
The central issue in this book are the federal ideas in the Zionist political thought during seventy years, from the early 1920s to the late 1990s. These ideas and plans had a double meaning and purpose: to find a suitable political bi-national structure for the Jews and Arabs in Palestine, which will enable both of them to fulfill their national goals, and to enable the Jewish people in the world to make Palestine their homeland by free immigration. The Zionist federative ideas were carried by different and even rival political parties and leaders, ranging from right-wing nationalists to Social-Democrats and liberal humanists. But, despite this diversity, all of them were based on the liberal and democratic political tradition in Europe before World War I. These ideas were renewed in the State of Israel at the end of the last century.